2009
DOI: 10.1152/ajpheart.01142.2008
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide production by NAD(P)H oxidase and mitochondria is increased in genetically obese and hyperglycemic rat heart and aorta before the development of cardiac dysfunction. The role of glucose-6-phosphate dehydrogenase-derived NADPH

Abstract: Serpillon S, Floyd BC, Gupte RS, George S, Kozicky M, Neito V, Recchia F, Stanley W, Wolin MS, Gupte SA. Superoxide production by NAD(P)H oxidase and mitochondria is increased in genetically obese and hyperglycemic rat heart and aorta before the development of cardiac dysfunction. The role of glucose-6-phosphate dehydrogenase-derived NADPH. Am J Physiol Heart Circ Physiol 297: H153-H162, 2009. First published May 8, 2009 doi:10.1152/ajpheart.01142.2008.-Increased oxidative stress is a known cause of cardiac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
117
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(134 citation statements)
references
References 58 publications
12
117
2
3
Order By: Relevance
“…Glucose-6-phosphate dehydrogenase (G6Pdh) activity was measured as described by Sepillion et al (105). ROS production was examined by measurement of hydrogen peroxide (H 2O2) or superoxide ion production.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose-6-phosphate dehydrogenase (G6Pdh) activity was measured as described by Sepillion et al (105). ROS production was examined by measurement of hydrogen peroxide (H 2O2) or superoxide ion production.…”
Section: Methodsmentioning
confidence: 99%
“…Third, glucose is not the preferred substrate of the myocardium and diabetes is known to further decrease glycolysis in the myocardium which should lower intracellular glucose concentrations (1,45,64). In contrast, significant increases in pentose shunt pathway activity have been reported that may significantly increase intracellular ROS (44,70,105). As a result it is unclear to what extent hyperglycemia may be a factor for promoting mitochondrial dysfunction as an underlying cause of diabetic cardiomyopathy.…”
mentioning
confidence: 99%
“…Furthermore, overexpression of G6PD in macrophages promotes oxidative stress and the expression of proinflammatory cytokines, which induce insulin resistance in adipocytes (24). Similarly, upregulation of G6PD in the liver, heart, and pancreatic b-cells of obese and diabetic animals also increases oxidative stress, which leads to functional defects in the respective tissues (12,25,26). Altogether, these findings suggest that anomalous G6PD upregulation in obese conditions might deteriorate energy homeostasis and oxidative stress, thereby accelerating metabolic complications.…”
mentioning
confidence: 98%
“…Studies proposed insulin resistance and increased mitochondrial fatty acid flux that predisposes cardiac mitochondria to ROS overproduction [23] . In addition to the more important and larger fraction of total cellular ROS that are generated in mitochondria, enzymatic system in cytosol, such as nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is also modulated by diabetes [24] . Increased oxidative stress causes cardiomyocyte cell damage, resulting in programmed cell death-apoptosis and fibrosis [25] .…”
Section: Increased Oxidative Stressmentioning
confidence: 99%